MRE11 and UBR5 Co-Operate to Suppress RNF168-Mediated Fusion of Dysfunctional Telomeres - Tang, Yongjian; Mukherjee, Joydeep; Pieper, Russell O. (Frontiers in Oncology, 2021)
TRF2 is part of the shelterin complex that hides telomeric DNA ends and prevents the activation of the cNHEJ pathway that can lead to chromosomal fusion. TRF2, however, also actively suppresses the cNHEJ pathway by recruiting two proteins, MRE11 and UBR5. MRE11 binds BRCC3, which in turn deubiquitinates γH2AX deposited at exposed telomeric DNA ends and limits RNF168 recruitment to the telomere. UBR5, in contrast directly ubiquitinates and destroys RNF168. The loss of telomeric RNF168 in turn blocks the subsequent recruitment of 53BP1 and prevents the cNHEJ-mediated fusion of chromosomes with exposed telomeric DNA ends. Although MRE11 and UBR5 are both involved in the control of telomeric RNF168 levels and the chromosome fusion process, their relative contributions have not been directly addressed. To do so we genetically suppressed MRE11 and UBR5 alone or in combination in glioma cell lines which we previously showed contained dysfunctional telomeres that were dependent on TRF2 for suppression of telomeric fusion, and monitored the effects on events associated with telomere fusion. We here show that while suppression of either MRE11 or UBR5 alone had minimal effects on RNF168 telomeric accumulation, 53BP1 recruitment, and telomeric fusion, their combined suppression led to significant increases in RNF168 and 53BP1 telomeric recruitment and telomeric fusion and eventually cell death, all of which were reversible by suppression of RNF168 itself. These results show that MRE11 and UBR5 co-operate to suppress fusion at dysfunctional telomeres.